Interplay of G-proteins and Serotonin in the Neuroimmunoinflammatory Model of Chronic Stress and Depression: A Narrative Review - Gusev, Evgenii; Sarapultsev, Alexey (Current Pharmaceutical Design, 2024)
Introduction: This narrative review addresses the clinical challenges in stress-related disorders such as depression, focusing on the interplay between neuron-specific and pro-inflammatory mechanisms at the cellular, cerebral, and systemic levels. Objective: We aim to elucidate the molecular mechanisms linking chronic psychological stress with low-grade neuroinflammation in key brain regions, particularly focusing on the roles of G proteins and serotonin (5-HT) receptors. Methods: This comprehensive review of the literature employs systematic, narrative, and scoping review methodologies, combined with systemic approaches to general pathology. It synthesizes current research on shared signaling pathways involved in stress responses and neuroinflammation, including calcium-dependent mechanisms, mitogen-activated protein kinases, and key transcription factors like NF-ΚB and p53. The review also focuses on the role of G protein-coupled neurotransmitter receptors (GPCRs) in immune and pro-inflammatory responses, with a detailed analysis of how 13 of 14 types of human 5-HT receptors contribute to depression and neuroinflammation. Results: The review reveals a complex interaction between neurotransmitter signals and immunoinflammatory responses in stress-related pathologies. It highlights the role of GPCRs and canonical inflammatory mediators in influencing both pathological and physiological processes in nervous tissue. Conclusion: The proposed Neuroimmunoinflammatory Stress Model (NIIS Model) suggests that proinflammatory signaling pathways, mediated by metabotropic and ionotropic neurotransmitter receptors, are crucial for maintaining neuronal homeostasis. Chronic mental stress can disrupt this balance, leading to increased pro-inflammatory states in the brain and contributing to neuropsychiatric and psychosomatic disorders, including depression. This model integrates traditional theories on depression pathogenesis, offering a comprehensive understanding of the multifaceted nature of the condition.
Keywords: pro-inflammatory cytokines